Checklist of seaweeds of Al-Hoceima National Park of Morocco (Mediterranean Marine Protected Area) - Moussa, Hanaa; Hassoun, Mustapha; Salhi, Ghizlane; Zbakh, Hanaa; Riadi, Hassane (Universidad de Málaga. Servicio de Publicaciones e Intercambio Científico, 2018)
The Mediterranean basin is a marine biodiversity hot spot. Despite this, the macroalgal diversity of the Mediterranean Sea is still not fully known, especially in the Mediterranean Marine Protected Areas (MPAs) including, Al-Hoceima National Park of Morocco (PNAH). This paper provides the first comprehensive checklist of the seaweeds of PNAH, based chiefly on our own original collections, and complimented by literature records. Using present-day taxonomy, the total number of taxa at both specific and infraspecific levels currently accepted is 306 taxa with 207 Rhodophyta (39 families), 51 Ochrophyta (13 families) and 48 Chlorophyta (12 families). Ninety five of these species were not found in our samples, 93 were new to the PNAH, and the taxonomic identity of 26 taxa was amended. From the totality of taxa, ten species were reported for the first time from Morocco: 9 Rhodophyta and one green alga. Furthermore, 12 others species (10 red, 1 brown and 1 green alga) are new records for the Mediterranean coast of Morocco. Besides this, confirmed records are mentioned for 20 species, whether in Africa, in Morocco or in the Moroccan Mediterranean coast. This accessible checklist to the international community could serve as an infrastructure for future algal investigations of the taxa in this Specially Protected Area of Mediterranean Importance.
Lista de algas marinas del Parque Nacional de Alhucemas en Marruecos (Área Marina Protegida del Mediterráneo)
Keywords: Algas marinas - Marruecos; Al-Hoceima National Park; Checklist; Mediterranean Marine Protected Areas; Morocco; Seaweeds; Algas marinas; Marruecos; Áreas Marinas Protegidas del Mediterráneo; Lista de algas; Parque Nacional de Alhucemas